2023
DOI: 10.1017/s136672892300024x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of visiting your home country: how brief reimmersion in their native country impacts migrants’ native language access

Abstract: The study explores how native language (L1) lexical access is affected by immersion in a second-language (L2) environment, and by short-term reimmersion in the L1 environment. We compared the L1 picture-naming performance of Polish–English bilinguals living in the UK (migrants) against that of bilinguals living in Poland (controls). Each group was tested twice: the migrants while in the UK (L2 immersion) and after visiting Poland (L1 reimmersion); the controls twice in their L1 environment. Contrary to our exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Evidence for heritage language reversal after re-immersion in the country of origin has been reported in two lines of bilingualism research. The first one relates to studies on first-generation bilingual adult speakers who are re-exposed to the heritage language through short-term visits (between 2 and 6 weeks per year) to the home country, either for study or for leisure (Chamorro et al, 2016;Genevska-Hanke, 2017;Gargiulo and van de Weijer, 2020;Casado et al, 2023). These studies have shown that the heritage language can be re-activated even after short re-immersion, leading to improved performance on structures that were vulnerable prior to re-immersion.…”
Section: Heritage Language Experiences Related To the Country Of Originmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence for heritage language reversal after re-immersion in the country of origin has been reported in two lines of bilingualism research. The first one relates to studies on first-generation bilingual adult speakers who are re-exposed to the heritage language through short-term visits (between 2 and 6 weeks per year) to the home country, either for study or for leisure (Chamorro et al, 2016;Genevska-Hanke, 2017;Gargiulo and van de Weijer, 2020;Casado et al, 2023). These studies have shown that the heritage language can be re-activated even after short re-immersion, leading to improved performance on structures that were vulnerable prior to re-immersion.…”
Section: Heritage Language Experiences Related To the Country Of Originmentioning
confidence: 99%
“…What is more, short-or long-term re-exposure to the native variety in the country of origin does not affect all language domains equally. Numerous studies have shown that structures that are more sensitive to input fluctuations, e.g., vocabulary (Casado et al, 2023;Gordon and Meir, 2023), as well as structures at the syntax-discourse interface, which may be more vulnerable to crosslinguistic pressure or influence (CLI) from the dominant language, may be more vulnerable in minority/heritage language acquisition contexts compared to syntactically conditioned structures (Argyri and Sorace, 2007;Daskalaki et al, 2019Daskalaki et al, , 2020. Whether or not these structures are equally re-activated after re-immersion in the country of origin seems to be a function of the length of re-immersion and the experimental task.…”
Section: Heritage Language Experiences Related To the Country Of Originmentioning
confidence: 99%
See 3 more Smart Citations